ATHENA: center of excellence in Cyprus in the field of remote sensing for cultural heritage in the areas of archaeology and cultural heritage - Hadjimitsis, Diofantos G.; Agapiou, Athos; Themistocleous, Kyriacos; Cuca, Branka; Nisantzi, Argyro; Lasaponara, Rosa; Nolè, Gabriele; Tucci, B.; Masini, Nicola; Krauss, Thomas; Cerra, Daniele; Gessner, Ursula; et al. (My University, 2016)
In periods of economic instability, national considerations are overruling the process of European integration. Cultural Heritage (CH) is an integral element of a European set of values, and respect for heritage is vital for developing a common European identity. The CH sector has always been facing a number of challenges that have increased with the financial crisis that has hit Europe. To name a few, these include the decrease of public budgets, urbanisation, globalisation, and technological changes. Within this context, CH professionals are seeking to improve currently used methodologies, in order to better understand, protect and valorise the common European past and common identity. The use of satellite and other remote sensing (RS) technologies has progressively been established in the field of environmental monitoring. In the domain of CH and landscape monitoring and in particular with regards to archaeological sites, these technologies have made a significant contribution to research and analysis over the past few decades. The potential use of RS for the understanding, documenting, monitoring and valorization of CH has long been recognised not only by RS experts and archaeologists, but also by the public authorities involved in heritage management, that suggested an increasing use of non-invasive technologies (Valletta Convention, 1992). The ATHENA project aims to strengthen the Cyprus University of Technology’s (CUT) Remote Sensing Science and Geo-Environment Research Laboratory in the field of Remote Sensing Archaeology by creating a unique link between two internationally-leading research institutions: The National Research Council of Italy (CNR) and the German Aerospace Centre (DLR). Through ATHENA, CUT’s staff research profile and expertise will be raised, while the S&T capacity of the linked institutions will come out enhanced.
Keywords: Remote sensing; Landsat; Cyprus; Fires; Monitoring